RNF7 Facilitated the Tumorigenesis of Pancreatic Cancer by Activating PI3K/Akt Signaling Pathway. (4th January 2023) - Hua, Hao; Xie, Huahua; Zheng, Jian; Lei, Linhan; Deng, Zilei; Yu, Chao
Abstract : RING finger protein-7 (RNF7) functions as a positive regulator in the progression of multiple malignancies. However, the underlying mechanism by which RNF7 contributes to pancreatic cancer (PC) is lacking. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to test the level of RNF7expression in PC cell lines and tissues. The role of RNF7 in PC tumorigenesis was analyzed by Cell Counting Kit-8 (CCK-8). 5-Ethynyl-20-deoxyuridine (EdU), wound-healing/Transwell assays, as well as a subcutaneous tumorigenesis model were constructed to assess the role of RNF7 in PC cells. The association between RNF7 and PI3K/Akt signaling were assessed by western blot and further confirmed by rescue experiments. The PC patients with upregulated expression of RNF7 had poor survival. Overexpression of RNF7 significantly facilitated PC proliferative and migrative and invasive properties in vitro and vivo; however, knockdown of RNF7exhibited the opposite results. Mechanistically, RNF7 promoted PANC-1 and SW1990 cell growth through impacting the activation of the PI3K/Akt signaling pathway. Our data demonstrated that RNF7 promoted PC tumorigenesis via activating the PI3K/Akt signaling pathway and might be regarded as one of the potential therapies to PC.